Incidence of G6PD Deficiency in a Tertiary Care Hospital in South India - Chandrashekhar, Chenna; Bandaru, Kasi (Journal of Nepal Paediatric Society, 2016)
Glucose-6-phosphate dehydrogenase (G6PD) deficiency is the commonest red cell enzymopathy affecting red cell metabolism. Its presentation can vary from drug induced haemolysis to neonatal jaundice with a prevalence ranging from 0-27% in India. The objective of this study was to find out the incidence of G6PD deficiency in babies delivered in our hospital and to assess its contribution in causing neonatal jaundice. 500 babies were screened for G6PD deficiency by Fluorescent spot test method. All the babies were found to have normal enzyme activity. Hence we concluded the burden of G6PD deficiency causing neonatal jaundice is less in our setup. J Nepal Paediatr Soc 2016;36(2):141-142.